Application Of Religious, Moral, Ethical And Traditional Values In Management - Andani, Salsabila Maisah; Junimar, Junimar; Ritonga, Diana Rosalina; Wijaya, Darma; Mujiatun, Siti (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2025)
The application of religious, moral, ethical and traditional values ​​in management is becoming increasingly relevant in the midst of integrity crises that often hit organizations. Various cases such as corruption, abuse of power, and exploitation of human resources show the urgent need to integrate these values ​​into every managerial process. Without a strong foundation of these values, the sustainability of the organization will be threatened, both in terms of reputation and long-term success. Religious values ​​provide a basis for moral and spiritual-based decision making, which supports the creation of an inclusive and ethical work culture. Ethical and moral principles play an important role in ensuring transparency, fairness and social responsibility in organizations. In addition, local traditions, such as mutual cooperation, deliberation, and family values, can be integrated into modern management systems to create a more contextual and humanistic approach. The research method in this paper uses a qualitative type of library design, with data collection methods collecting reading books, journals and other electronic references. This is done by analyzing primary data from main references and secondary data from supporting references. The aim is to explain how religious values ​​can be implemented in management practices, analyze the role of morals and ethics in increasing organizational effectiveness, explore the integration of local traditions into modern management systems, and provide examples of the application of these values ​​in developing the socio-cultural competence of State Civil Apparatus. (ASN) in Aceh and North Sumatra.